Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Perusahaan Jasa Ekspedisi Krian) - Bayu Putra Setiawan; Agus Frianto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Customer satisfaction in using services or services is influenced by price. The appeal of products or services cannot be released from prices such as money, time, cognitive activity, behavioral efforts, value and pricing. Prices are often used as a value indicator if the price is linked to a perceived benefit on an item or service. The producers or sellers strive to fulfill their needs and wishes and provide maximum satisfaction to the consumer. Customer satisfaction in using services or services is influenced by the price and quality of service. This research is done with quantitative, Data used primary and secondary data, research samples as many as 30 subscribers, The study used multiple linear regression analyses. The testing technique in this study is validity and reliability test, while the data analysis technique uses classical assumption test (normality test, heteroskedastisity, Multicolonierity, autocorrelation, Linieritas), while hypothesis test is T test, F test and coefficient of determination.. The results showed that: (1) The price has significant effect on customer satisfaction at Jasa Ekspedisi Krian. (2) Service quality has significant effect on customer satisfaction Jasa Ekspedisi Krian (3) The price and quality of service are simultaneously influential for customer satisfaction Jasa Ekspedisi Krian. Keyword: Price; Service Qualit; Customer Satisfaction